ANALISIS PERHITUNGAN DAN PELAPORAN PPH 22, PPH 23, PPH 25 PADA PT. MODERN JAYA FARMA - Tiran, Elsi Yefia; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to determine the calculation and reporting of PPh Article 22, PPh Article 23 and PPh Article 25 at PT. Modern Jaya Farma 2020. Data collection was obtained from interviews and documentation. The type of research used is a case study with quantitative methods. The results of this study stated that PT. Modern Jaya Farma has performed its tax obligations by calculating and reporting Income Tax Article 22 carried out by third parties. The calculation of Income Tax Article 23 is in accordance with the applicable tax provisions. The deposit and reporting of Income Tax Article 23 is not in accordance with the applicable tax provisions due to errors and delays in making the deposit. Reporting. Income Tax Article 25 is in accordance with the applicable tax provisions.